Pengaruh Persepsi Penggunaan dan Persepsi Risiko Terhadap Minat Menggunakan Dompet Digital Melalui Aplikasi Shopeepay Sebagai Alat Pembayaran Non-Tunai Pada Generasi Z - Clara Alvinasari Agestha; Djoko Kristianto (LPPM Universitas Sains dan Teknologi Komputer, 2025)
The rapid growth of financial technology has led to the emergence of digital wallets as an efficient and practical means of payment. One of the most widely used services in Indonesia is Shopeepay, particularly among Generation z, who are known for their adaptability to new technologies. This study aims to examine to influence of perceived usefulness (X1) and perceived risk (X2) on the intention to use digital wallets (Y), with Shopeepay payment method (M) as a moderating variable. This research employed a quantitative approach by distributing questionnaires to 60 University students who actively use Shopeepay. The collected data were analyzed using multiple linier regression and Moderated Regression Analysis (MRA). The findings reveal that perceived usefulness has a positive and significant effect on the intention to use Shopeepay (sig. 0,004<0,05). Perceived risk also shows a significant effect in thr multiple regression test (sig. 0,003<0,05), but becomes insignificant when tested with MRA (sig. 0,094>0,05). This suggests that impact of risk tends to weaken when moderated by the payment methode. Furthermore, the Shopeepay payment method itself does not significantly influence user intention (sig. 0,067>0,05) collectively, perceived usefulness and perceived risk significantly affect the intention to use Shopeepay (sig. 0,001).